Hydrolysis of phytic acid and its availability in rabbits - Marounek, M; Dusková, D; Skrivanová, V (The British journal of nutrition, 2003)
Twenty weaned rabbits were fed ad libitum two granulated feeds containing lucerne meal, barley, oats, wheat bran, oilseed meals and sugarbeet pulp in different proportions. Phytate P in these feeds represented 28.6 and 29.3 % of the total P. Digestibility trials were carried out in rabbits 7 and 10 weeks old. Digestibility of phytate P was 82.1 %, on average. Apparent digestibility of total P was 48.1 and 35.5 % in rabbits aged 7 and 10 weeks, respectively. Concentration of P in the faecal DM of these rabbits averaged 11.9 and 14.7 mg/g. Most of the faecal P was phosphates P (68.1 %). Proportion of phytate P in total faecal P was 9.0 %. Age effect on total P digestibility and faecal P concentration was significant (P<0.05). In five in vitro experiments twenty-four rabbits were killed at the age of 11 weeks, digesta samples diluted with physiological saline containing phytic acid and incubated anaerobically. Calculations of phytase activity in segments of the digestive tract were based on the estimation of phytic acid hydrolysed during the first 2 h of incubation. The caecum contained 58.6 % of the phytase activity of the digestive tract. Corresponding relative values for the phytase activity in the stomach, small intestine and colon were 22.3, 7.7 and 11.4 %, respectively. In incubations of the caecal contents, phytic acid was hydrolysed more rapidly at pH 5-6 than in the neutral pH region. The hydrolysis was inhibited by Ca cations, and to a small extent also by phosphate anions. Commercial fungal phytase (Natupho) was highly active in incubations of the contents of the stomach at pH 1.9. It can be concluded that phytic acid is hydrolysed quite efficiently in the digestive tract of rabbits. This hydrolysis occurred mainly in the caecum. Absorption of soluble inorganic phosphates in the gut is incomplete.
Keywords: 6-Phytase; 6-fytasa; Feces; Animal Nutritional Physiological Phenomena; fyziologie výživy zvířat; střeva; Gastrointestinal Contents; Male; gastrointestinální obsah; Digestion; Animal Feed; žaludek; Stomach; cékum; Hydrogen-Ion Concentration; mužské pohlaví; krmivo pro zvířata; Cecum; Phytic Acid; králíci; koncentrace vodíkových iontů; Animals; ženské pohlaví; zvířata; Rabbits; Intestines; Female; feces; trávení; kyselina fytová